Optimization study on the uniform temperature of an additively manufactured cooler for a semiconductor heating device. (5th May 2023) - Lee, Seung Yeop; Kim, Kun Woo; Kim, Da Hye; Yang, Min Seok; Kim, Ji Wook; Choi, Geuna; Lee, Jae Wook; Park, Il Seouk
Highlights: Thermofluidic effects on lattice were investigated in varied flow speed and design. Optimum design for uniform temperature was developed based on surrogate model. The temperature uniformity of the cooler was enhanced by 83.4%. Abstract: A semiconductor heating device is the core component of the apparatus used for testing semiconductor dies. It is important to heat semiconductor dies at a uniform temperature. The surface temperature of the cooler, which is a component of the heating device, directly affects heating temperature uniformity. Thus, a uniform temperature of the cooler enables uniform heating of semiconductor dies. In this study, we developed an optimization method for achieving temperature uniformity in coolers, using an approach based on a surrogate model. The technique developed in this study simplified the conjugate heat transfer in the channel network of a cooler. A body-centered cubic lattice core was adopted for the local augmentation of heat-transfer performance within the internal channel of the cooler. To reveal the effects of the flow speed and lattice column diameter on the pressure drop and heat transfer, a computational fluid dynamics simulation was implemented using a central composite design, with the Reynolds number and diameter ratio varying in the ranges of 3078–23852 and 0.0869–0.313, respectively. The surrogate model was defined after the dimensional analysis of a single channel and circuit analogy. A particle swarm optimization algorithm was adopted to determine the optimal column diameters of each lattice structure based on the surrogate model. The optimization of the cooler of the semiconductor heating device was assessed by comparing it with a model consisting of only identical lattices in each position. The results showed a prominent enhancement, wherein the deviation in the temperature was reduced by 83.4%.